Current Account Surpluses and the Interest Rate Island in Switzerland - Mauro, Paolo (International Monetary Fund, 1995)
This paper describes some long-run aspects of the Swiss balance of payments, highlighting two macroeconomic phenomena that make Switzerland stand out among other countries: first, it has had a persistent current account surplus and the largest ratio of net foreign assets to GDP in the world; second, its real interest rates have been significantly lower than those of most other industrialized countries, earning it the label "interest rate island". These two distinctive features may be related, and ultimately both may result from an excess of national savings over investment for many years. The real interest differential may largely be attributed to a foreign exchange rate risk premium, which compensates Swiss residents for holding net assets in foreign currency and foreign residents for bearing net liabilities in Swiss francs